ANALISIS STRATEGI BERSAING BISNIS JASA OLAHRAGA (KASUS PERSAINGAN BISNIS JASA PENYEWAAN LAPANGAN FUTSAL DI PEKANBARU) - Ika Lestari; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
At this point in Pekanbaru futsal business increasingly in the interest can be seen with the development of futsal existing business. To expand its business at a higher level the company must carry out all activities in the areas of operations, marketing, finance, production, and other fields that exist in the company. The purpose of this study was to determine and analyze the sports service business competitive strategy rental futsal field in Pekanbaru. The methods used in this research is descriptive and analytical techniques used are qualitative analysis. Methods of data collection using questionnaires. The questionnaire is the technique of data collection is done by providing a set of written questions to the respondent’s in charge. The sample is part of the number and characteristics of the population is owned by as many as 40 business owners futsal. The results of this research is the analysis of both cost leadership strategy to obtain a score of 1118 and the analysis of differentiation strategies to obtain a score of 1223 so it can be deduced that more strategies applied by a health services business (business competition case futsal rental service s in Pekanbaru) is a strategy differentiation. keywords : Analysis, competitive strategy, leasing service futsal court